Aspect and thematic suffixes in Şavşat Georgian - Okumuş, Reyhan Lütfiye. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study investigates the morpho-syntactic features of Thematic Suffixes (TS) in Şavşat Georgian, a non-literal dialect of Georgian spoken in the northeast of Turkey. Specifically, it aims to provide an analysis on the different realisations of TS and relate these realisations with Aspect. For this purpose, we first comprehensively describe the environments in which Thematic Suffixes -ob, -eb, -av and -ev appear. Verbs with different Aktionsart features are examined in various tense conjugations. As a result of this analysis, it is argued that the presence of TS denotes imperfectivity in Şavşat Georgian. Besides, each realisation of TS specifically denotes a certain lexical aspectual class; that is, -eb denotes states, -av denotes activity, -eb denotes change of state and -ev denotes two-phase achievements. To complete the discussion on morphosyntactic features of the Thematic Suffixes, we offer a syntactic analysis based on a two-layered Aspect head following Travis (2010). In such a mechanism, TS is base generated in Inner Aspect head to mark the lexical aspectual class of the verb and then it moves into Outer Aspect head to check imperfectivity. Causative construction is also accounted for with a similar mechanism in which a certain realisation of TS, i.e. -eb, always occurs.
Keywords: Georgian languages -- Suffixes and prefixes.; Georgian language -- Shavshat (Turkey); Frames (Linguistics) -- Georgian language -- Shavshat (Turkey)